2013
DOI: 10.1373/clinchem.2012.199794
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Insulin Analysis Using Liquid Chromatography–Tandem Mass Spectrometry in a High-Throughput Clinical Laboratory

Abstract: BACKGROUND Circulating insulin concentrations reflect the amount of endogenous insulin produced by the pancreas and can be monitored to check for insulin resistance. Insulin is commonly measured using immunochemiluminometric assays (ICMA). Unfortunately, differing crossreactivities of the various ICMA antibodies have led to variability in assay results. In contrast, liquid chromatography–tandem mass spectrometry (LC-MS/MS)-based approaches can provide a highly specific alternative to immunoas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 20 publications
2
49
0
Order By: Relevance
“…When an assay reports concentrations on a population of samples that have very little bias when compared with a reference measurement procedure (i.e., a robust assay with rigorous process controls that uses certified or standard reference materials in its calibration), the assay is said to be standardized. It is possible to harmonize and standardize immunoassays or mass spectrometric assays (74). …”
Section: Reference Materials: Improving the Harmonization Of Protein mentioning
confidence: 99%
“…When an assay reports concentrations on a population of samples that have very little bias when compared with a reference measurement procedure (i.e., a robust assay with rigorous process controls that uses certified or standard reference materials in its calibration), the assay is said to be standardized. It is possible to harmonize and standardize immunoassays or mass spectrometric assays (74). …”
Section: Reference Materials: Improving the Harmonization Of Protein mentioning
confidence: 99%
“…On the one hand, insulin has a high biological variability (within-and between-subject variability of 21.1% and 58.3% respectively), 4 and on the other hand, its measurement has yet to be standardized. 5,6 These two aspects have a direct impact on the estimation of IR using the HOMA-IR index and other formulas which have been developed using insulin level in their calculations (QUICKI, FGIR, Raynaud, reciprocal insulin). 7 Because of these difficulties, attempts have been made to identify other parameters that could be helpful for assessing IR.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a 0.1% formic acid aqueous solution and acetonitrile improved the detection sensitivity of peptide quantitation. [23][24][25][26][27] However, in this work, our comparison revealed that methanol was better than acetonitrile in terms of sensitivity, and that a low acetic acid concentration (0.01%) was preferable over the use of formic acid. In general, acetonitrile is used in ESI ionization, because an organic solvent with low viscosity and a low boiling point is preferred for ionization.…”
Section: Mass Spectra For Selecting the Ion Transition For Lc-ms/msmentioning
confidence: 56%